2007
DOI: 10.1007/s10329-007-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Body mass of wild ring-tailed lemurs in Berenty Reserve, Madagascar, with reference to tick infestation: a preliminary analysis

Abstract: In 1999, we measured the body mass of 101 wild ring-tailed lemurs (Lemur catta) inhabiting the Berenty Reserve, Madagascar. In addition, we counted the number of ticks [Haemaphysalis (Rhipistoma) lemuris Hoogstraal, 1953] infesting their facial skin and external auditory meatuses. For both males and females, the body mass appeared to increase until the age of 3 years. With the apparent exception of infants, there were no sexual differences in body mass. Within a group, higher-ranked adult males tended to be he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…In total, 18 animals surpassed the mean body mass range for free-living ring-tailed lemurs of 2-2.5 kg (Sussman 1991;Drea and Weil 2008), yet our age-body mass graph ( Fig. 1) largely resembled that given by Koyama et al (2008), and only two animals appeared to be of excessive weight for their age, being distinctively above maximum weights recorded in the natural habitat of 2.6 kg by Simmen et al (2010). These findings suggested that obesity was not a major factor in the study populations.…”
Section: Methodsmentioning
confidence: 64%
“…In total, 18 animals surpassed the mean body mass range for free-living ring-tailed lemurs of 2-2.5 kg (Sussman 1991;Drea and Weil 2008), yet our age-body mass graph ( Fig. 1) largely resembled that given by Koyama et al (2008), and only two animals appeared to be of excessive weight for their age, being distinctively above maximum weights recorded in the natural habitat of 2.6 kg by Simmen et al (2010). These findings suggested that obesity was not a major factor in the study populations.…”
Section: Methodsmentioning
confidence: 64%
“…Thus, we cannot rule out the possibility that social dominance is associated with increased energy input or energy conservation at other seasons or that inter-individual variation in TEE within each sex was accidentally confounded with the particular social status of the focal animals. For example, Koyama et al [69] found in a large sample at Berenty that, in autumn, body weight of ring-tailed lemur males varied across hierarchical ranks, suggesting different TEEs were mediated by social relationships. However, they did not find significant differences in body weight among females of different status.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the animals forage on over 15 species of flora that grow in the enclosures [Ganzhorn, 1986]. Furthermore, the average weights (2.32 kg for females and 2.36 kg for males), and thus, net caloric intake of the adult lemurs at DLC were comparable to those of wild ringtailed lemurs [2.21 kg both genders, Sussman 1991; 2.27 kg females, 2.22 kg males, Koyama et al, 2007].…”
Section: Subjectsmentioning
confidence: 99%